Síntese, Caracterização Estrutural e Propriedades Luminescentes de Complexos de Lantanídeos (III) com Hidrazonas e Semicarbazonas derivadas da 2,6-Diformilpiridina e com Triazenos 1-óxidos. - Machado, Aline (2011)
Lanthanide complexes with ligands containing oxygen and nitrogen as donor atoms have been investigated in this study aiming to explore the coordinative behavior of metals with high coordination numbers, as well as a study of luminescence properties of new complexes. The chosen ligands were hydrazones and semicarbazones derived from 2,6-diformylpyridine and triazenes -1-oxide. Sixteen crystal structures were obtained, among these ten were characterized and presented in this final thesis for a doctorate. Many were found as monomers and dimers, demonstrating the versatility in the manner and the coordination geometry of the metal centers and ligands used in the formation of complexes. The coordination numbers in the structures ranged from 8 to 10, forming very unusual coordination polyhedra and intermediaries to other known geometries. From all crystal structures, only two complexes presented luminescence and only with one of them it was possible to develop a study experimenthal bases and theoretical calculations compared with the X-ray diffraction.